Double Jeopardy and Multiple Sovereigns: A Jurisdictional Theory - Anthony J. Colangelo (Washington University Law Review, 2009)
This Article offers a coherent way of thinking about double jeopardy rules among sovereigns. Its theory has strong explanatory power for current double jeopardy law and practice in both U.S. federal and international legal systems, recommends adjustments to double jeopardy doctrine in both systems, and sharpens normative assessment of that doctrine. The Article develops a jurisdictional theory of double jeopardy under which sovereignty signifies independent jurisdiction to make and apply law. Using this theory, the Article recasts the history of the U.S. Supreme Court's “dual sovereignty” doctrine entirely in terms of jurisdiction, penetrating the opacity of the term “sovereign” as it is often deployed by the Court and supplying a useful analytical predictor for future extension of the doctrine. The Article then applies the theory to the international legal system to explain the confused and seemingly dissonant body of modern international law and practice on double jeopardy, including the tribunal statutes, and the exercise of universal jurisdiction. The Article next explores the theory's implications for U.S. and international law in light of two main double jeopardy concerns: the individual right to be free from multiple prosecutions, and the sovereign ability to enforce law. It argues that since the U.S. dual sovereignty doctrine originally derived and continues to derive justification from the sovereign's jurisdiction over the defendant, the Court's present analysis is incomplete and betrays the doctrine's own foundations by ignoring a basic, and necessary, constitutional inquiry: whether a successively prosecuting sovereign's exercise of jurisdiction satisfies due process. This inquiry would enrich present doctrine by incorporating individual rights concerns — concerns that are now completely absent from dual sovereignty analysis — and holds the potential to alter outcomes, especially in cases of successive prosecutions between U.S. states and by the federal government when it exercises jurisdiction extraterritorially. The theory similarly enriches international doctrine through a reasonableness evaluation of a successively prosecuting nation-state's jurisdiction that resembles U.S. due process tests. Finally, the Article suggests that where multiple sovereigns legitimately may exercise jurisdiction, it does not mean that they will; institutionalized comity mechanisms between enforcement authorities of different sovereigns can accommodate both the sovereign interest to enforce law and the individual interest to be free from multiple prosecutions by encouraging the representation of multiple sovereigns' interests in a single prosecution in a single forum.
Keywords: Double jeopardy; Dual sovereignty; Human rights; Jurisdiction (International Law); War (International Law)